High-pressure granulites in the Fuping Complex of the central North China Craton: Metamorphic P–T–t evolution and tectonic implications. (1st April 2018) - Qian, Jiahui; Yin, Changqing; Zhang, Jian; Ma, Li; Wang, Luojuan
Graphical abstract: Highlights: Mafic granulites in Fuping experienced a peak stage of metamorphism under 12–13 kbar/760–800 °C. Cooling of the granulites occurred at 1.85–1.89 Ga. HP granulites in Fuping witnessed a protracted Paleoproterozoic orogeny in the central North China Craton. Abstract: Mafic granulites in the Fuping Complex occur as lenses or boudins within high-grade TTG (Trondhjemite–Tonalite–Granodiorite) gneisses. Petrographic observations reveal four generations of mineral assemblage in the granulites: an inclusion assemblage of hornblende + plagioclase + ilmenite + quartz within garnet core; an inferred peak assemblage composed of garnet ± hornblende + plagioclase + clinopyroxene + rutile/ilmenite + quartz; a decompression assemblage characterized by symplectites of clinopyroxene ± orthopyroxene + plagioclase, coronae of plagioclase ± clinopyroxene ± hornblende around embayed garnet porphyroblasts or a two-pyroxene association; and a late amphibolite-facies retrogressive assemblage. Two representative samples were used for pseudosection modeling in NCFMASHTO model system to determine their metamorphic evolution. The results show that these granulites experienced a high-pressure stage of metamorphism with peak P–T conditions of 12–13 kbar and 760–800 °C (Pmax ) and a post-peak history under P–T conditions of ∼9.0 kbar and 805–835 °C (Tmax ), indicating a nearly isothermal decompression process (ITD) with a slight heating. Metamorphic evolution from the Pmax to the Tmax is predicted to be dominated by garnet breakdown through continuous metamorphic reactions of garnet + quartz ± diopside = hornblende + plagioclase + liquid and garnet + quartz + hornblende = plagioclase + diopside + liquid + orthopyroxene. Further metamorphic evolution after the Tmax is dominated by cooling, suggesting that high-pressure (HP) granulites may also exist in the Fuping Complex. Metamorphic zircons in the Fuping HP mafic granulites have left inclined REE patterns, Ti contents of 1.68–6.88 ppm and crystallization temperatures of 602–712 °C. SIMS zircon U–Pb dating on these zircons yields 207 Pb/ 206 Pb ages of 1891 ± 14 Ma and 1849 ± 6 Ma, interpreted to represent the cooling stage of metamorphism. The P–T–t evolution of the Fuping HP mafic granulites records well the protracted Paleoproterozoic orogenic event occurred in the central North China Craton.